Optimalisasi Layanan Handling Complaint di Rumah Sakit Umum Al-Islam H.M Mawardi Krian Sidoarjo - Sari, Ika Puspita; Yusmanisari, Eka; Arwani, M.; Huda, Nurul; Sulistyawati, Ety Diana (STIKES Yayasan RS.Dr.Soetomo, 2023)
Community service activities are activities that include efforts to improve the quality of human resources, including broadening insights, knowledge and improving skills carried out by the academic community. The implementation of these activities is divided into 3 activities, namely lectures, discussions and case studies. The purpose of this community service is to increase knowledge about how effective communication techniques can be applied in handling patient complaints at the hospital, and how this can improve the quality of service at Al-Islam H.M Mawardi General Hospital. The results obtained from this community service activity are: communication ethics in handling patient complaints at Al-Islam H.M Mawardi Hospital, namely: conveying apologies to patients, explaining the main causes of patient complaints, offering solutions to patient complaints, reconfirming the patient's willingness to accept the solutions offered, offer alternative solutions for handling patient complaints, express gratitude for the patient's willingness to accept alternative solutions, and provide complete information about the hospital's excellent service standards